Improving air quality in Guangzhou with urban green infrastructure planning: An i-Tree Eco model study. (1st October 2022) - Yao, Yibo; Wang, Yafei; Ni, Zhuobiao; Chen, Shaoqing; Xia, Beicheng
Abstract: With rapid economic development and increasing population, the urbanization process is accelerated, and serious air pollution threatens human health. Urban green infrastructure (UGI) planning has proven effective in improving air quality. However, how to improve air quality through UGI planning in different urban forms remains unclear. Therefore, based on the local climate zone (LCZ) of Guangzhou, this study used the i-Tree Eco model to evaluate the removal efficiency of air pollutants under different UGI designs. The results showed that from 2013 to 2019, the Built Type LCZ gradually replaced the Land Cover Type in Guangzhou, indicating the rapid urbanization process. The air pollution of the Built Type LCZs was more serious than that of the Land Cover Type. Roadside green space was more effective for air quality improvement when applied on a larger scale with the more addable area, while applying city park green space was an alternative at a local scale with limited area. The optimal designs of UGI varied within different LCZs. Adding street trees and shrubs by 20% in the urban expansion area was the optimal design for LCZ 6. For LCZ 4, adding 20% of city park trees in the urban expansion area and 5% of overall shrubs were optimal. This study proposed a practical approach for colligating the LCZ concept and i-Tree Eco simulation for air quality improvement.